Towards a knowledge model bridging technologies and applications in cultural heritage documentation - Boochsa, F. (2020)
This paper documents the formulation of an international, interdisciplinary study, on a concerted European level, to prepare an innovative, reliable, independent and global knowledge base facilitating the use of today’s and future optical measuring techniques for the documentation of cultural heritage. Cultural heritage professionals, color engineers and scientists share similar goals for the documentation, curation, long-term preservation and representation of cultural heritage artifacts. Their focus is on accuracy in the digital capture and remediation of artefacts through a range of temporal, spatial and technical constraints. A shared vocabulary to interrogate these shared concerns will transform mutual understanding and facilitate an agreed movement forward in cultural heritage documentation here proposed in the work of the COST Action Color and Space in Cultural Heritage (COSCH). The goal is a model that captures the shared concerns of professionals for a standards-based solution with an organic Linked Data model. The knowledge representation proposed here invokes a GUI interface for non-expert users of capture technologies, facilitates, and formulates their engagement with key questions for the field.